The way of Qu‐making significantly affected the volatile flavor compounds in Huangjiu (Chinese rice wine) during different brewing stages. Issue 7 (7th April 2022) - Peng, Qi; Zheng, Huajun; Meng, Kai; Zhu, Yimeng; Zhu, Wenxia; Zhu, Hongyi; Shen, Chi; Fu, Jianwei; Elsheery, Nabil l.; Xie, Guangfa; Han, Jiongping; Wu, Peng; et al.
Abstract: The volatile flavor compounds of Huangjiu (Chinese rice wine) brewed from different raw materials were obviously different, but there were few studies on the volatile flavor compounds of Huangjiu brewed from different wheat Qu at different brewing stages. In this paper, headspace–solid phase microextraction combined with gas chromatography–mass spectrometry, combined with principal component analysis and sensory evaluation, was used to determine the volatile flavor compounds in Huangjiu brewed from wheat Qu made by hand and wheat Qu made by mechanical. The results showed that there were significant differences in the contents and types of volatile flavor substances in Huangjiu brewed from different wheat Qu at fermentation stages, and the prefermentation and postfermentation Huangjiu samples could be well distinguished from each other. Compared with the Huangjiu brewed from wheat Qu made by mechanical, the Huangjiu brewed from wheat Qu made by hand has stronger aroma and better taste. Abstract : In this paper, headspace–solid phase microextraction combined with gas chromatography–mass spectrometry (HS–SPME–GC–MS), combined with principal component analysis (PCA) and sensory evaluation, was used to determine the volatile flavor compounds in Huangjiu (Chinese rice wine ) brewed from wheat Qu made by hand and wheat Qu made by mechanical. The results showed that compared with the Huangjiu brewed from wheat Qu made by mechanical, the Huangjiu brewed from wheat Qu made by hand has stronger aroma and better taste.